MS Glow and PS Glow: A Forensic Linguistics Study (e-Journal of Linguistics, 2023)
The feud between PS Glow and MS Glow became a conversation thatcaught the public's attention. One of the parties is considered to havethe same principal trademark, so the intention to imitate, plagiarize orfollow the other party's brand for business purposes creates unhealthybusiness conditions and deceives or misleads consumers. This studyanalyzes the trademark dispute between PS Glow and MS Glow. Thedata sources in this study are the Decisions of the Supreme Court of theRepublic of Indonesia Number 2/Pdt.Sus.HKI/Merek/2022/PN NiagaMdn and Number 2/Pdt.Sus.HKI/Merek/2022/PN Niaga Sby. Thisresearch uses methods and techniques which are divided into threestages, namely (1) the data collected by observation method assisted bynote-taking technique; (2) Data analysis using qualitative methods. Thedata analysis technique used descriptive technique; and (3) Presentationof the data analysis results using informal and formal methods. Theresults show that PS Glow and MS Glow are other trademarks. It can beseen based on the analysis at the phonological level, namely thepresence of sounds that can distinguish meaning, namely /p/ - /m/.Thus, it can be said that the decisions of judges are consideredinaccurate.
Keywords: Forensic Linguistics; Trademark; MS Glow and PS Glow